Teaching Methods and Creativity in Vocational Education: A Case Study of SMK Negeri 3 Bandung - Rina Hergisa (RSF Press, 2025)
Vocational education plays a crucial role in preparing students for the creative economy, requiring teaching methods that not only build technical competencies but also foster creativity and socio-cultural innovation. However, little is known about how these pedagogical strategies are implemented in Indonesian vocational schools, particularly within the arts and creative economy fields. This study explores how teaching methods in the Creative Arts and Creative Economy programs at SMK Negeri 3 Bandung support students’ creativity and socio-cultural innovation. Using a qualitative exploratory design, data were collected through interviews and focus group discussions with 7 teachers and 15 students, selected via purposive sampling. Thematic analysis was applied to identify patterns, supported by triangulation across teacher and student perspectives, and assisted with NVivo software to enhance systematic coding and analysis. Four interrelated themes emerged: (1) diverse and participatory teaching methods; (2) creativity as a core outcome fostered through experimentation and tolerance of failure; (3) integration of socio-cultural heritage into modern projects; and (4) teachers acting as facilitators of innovation, while addressing challenges such as limited resources, time constraints, unequal participation, and varied student preferences. The findings confirm and extend existing theories of creativity, socio-cultural learning, and 21st-century skills, while highlighting the importance of balancing autonomy with structured guidance. Beyond education, the study contributes to broader social science and management discussions by showing how culturally grounded pedagogical practices can enhance innovation capacity and human capital development in the creative economy. Practically, the study recommends training teachers in flexible pedagogy, enhancing digital resources, allowing more time for inquiry, and embedding cultural heritage into vocational education.